Scattering problem for Dirac system with nonlocal potentials - Cojuhari, P. A.; Nizhnik, L. P. (Methods of Functional Analysis and Topology, 2019)
For a Dirac system on the half-axis, we obtain an explicit expression for the scattering operator in terms of a nonlocal potential.